A inclusão de pessoas com deficiência visual nas aulas de educação física em escolas municipais da cidade de Castanhal-PA - TAVARES, Vilson Guedes (2019)
Deficiency has existed since ancient history, and over time its concepts and forms of acceptance have undergone several changes. At present there are several laws that promote conditions of equality and social inclusion for the disabled person. Vision impairment involves low vision and blindness and can be classified as mild, moderate, severe or profound and its causes may be diverse, but do visually impaired students experience difficulties in attending physical education classes? The present study is characterized as qualitative and sought to analyze the inclusion of students with visual impairment in the physical education classes of the municipal schools of Castanhal-PA, through their own conceptions of inclusion. Four students with visual impairment participated, two male and two female, between the ages of 13 and 18, attending elementary school. A questionnaire was applied with 14 questions where responses were recorded through a cellular device. Students link inclusion with their participation in classes and although they feel included, they suggest changes and adaptations so that they can have quality classes and, consequently, have a better school performance.